1998
DOI: 10.1016/s0361-9230(98)00097-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different conditions for tilt compensation on symptoms of motion sickness in tilting trains

Abstract: Increased speeds of trains can be achieved by using tilting trains that decrease the lateral acceleration experienced by passengers on curves, thereby allowing trains to run typically 25-30% faster on existing curved track and maintaining good ride comfort. Unfortunately, motion sickness in tilting trains is a major problem for some passengers. To investigate the incidence of motion sickness and the extent to which different tilt compensation strategies influence its occurrence, tests were conducted with a til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 9 publications
1
29
0
11
Order By: Relevance
“…Several methods have been employed to find out the underlying cause of motion sickness, and research has shown that passengers complain the most when the train uses a passively tilted system. Actively tilting train does record motion sickness cases however the numbers coincide closely with non-tilting trains [4].…”
Section: Literature Studymentioning
confidence: 79%
See 3 more Smart Citations
“…Several methods have been employed to find out the underlying cause of motion sickness, and research has shown that passengers complain the most when the train uses a passively tilted system. Actively tilting train does record motion sickness cases however the numbers coincide closely with non-tilting trains [4].…”
Section: Literature Studymentioning
confidence: 79%
“…Motion sickness is not necessarily uncommon in the transportation industries. Non-tilting trains, although not as much as tilting trains, have reported passengers experiencing motion sickness [4]. There is currently a general understanding that having tilting trains which compensate for 100 % of lateral acceleration poses high risks of inducing motion sickness [4].…”
Section: Literature Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Branton (1993b), Fo¨rstberg (1997Fo¨rstberg ( , 2000, Fo¨rstberg et al (1998), Suzuki et al (1999), Suzuki and Shiroto (2002), van der Weide (1999). Support for passengers also comes through the interfaces to the information and ticketing systems with which they are provided (Davis and Mills, 2005;Garnerin, 2001;Lamel et al, 2002;Thimbleby et al, 2002), and with designing for their movement around stations and in boarding and alighting trains (Morlok et al, 2004).…”
Section: Rail Human Factors Research To Datementioning
confidence: 99%